Efficacy of 3D Laparoscopy in Thoraco-Laparoscopic Esophagectomy for Caustic Esophageal Strictures - Toktogaziev, Bakyt; Omorov, Rahatbek; Kurmanbekov, Nurtilek; Belekov, Tilek; Karabaev, Azamat; Sharshenbaeva, Aizhamal; Vityala, Yethindra (ENT Updates, 2025)
Ingesting caustic substances can cause severe esophageal strictures, particularly in young adults. Thoraco-laparoscopic esophagectomy (TLE) is a minimally invasive surgical treatment for complex strictures when conservative methods fail. However, dense fibrosis and altered anatomy pose challenges for conventional laparoscopic surgical systems. This prospective comparative study evaluated the effectiveness of three-dimensional (3D) laparoscopic visualization in TLE for post-burn esophageal strictures. Twenty-eight patients aged 18–40 years with caustic-induced strictures were divided into two groups: Full High-Definition (HD) laparoscopy (n = 14) and 3D laparoscopy (n = 14). Intraoperative and postoperative outcomes were compared between the two groups. The 3D group had significantly shorter operative times (200 ± 10 min vs. 230 ± 20 min; p < 0.05), reduced blood loss (40 ± 8 ml vs. 60 ± 10 ml; p < 0.05), and lower anastomotic failure rates (7.1% vs. 21.4%; p < 0.05) than the Full HD group. Postoperative complications and hospital stay were lower in the 3D group, although the difference was not statistically significant. Surgeon feedback indicated better depth perception and precision with 3D systems. Macroscopic examination of the resected specimens confirmed severe fibrotic strictures, whereas postoperative imaging showed patent anastomoses. The results suggest that 3D laparoscopy enhances surgical efficiency and safety in TLE for post-caustic strictures by improving visualization of the fibrotic planes. Incorporating 3D systems into surgical practice and training can potentially improve outcomes and expand minimally invasive techniques for complex esophageal surgeries, particularly in resource-limited settings.